Assessment of selected elements of healthcare in the opinion of healthcare workers - Niemczyk, Agata; Adler, Donata; Handzel, Jarosław A.; Gródek-Szostak, Zofia; Siguencia, Luis Ochoa (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The healthcare system is an important part of the functioning of any country. A special role in this system is played by the personnel — especially medical, but also non-medical personnel, who perform their tasks based on the available resources. The article considers the opinions of healthcare workers about selected elements of this system proposed by Zgliczyński. The opinions of employees regarding the current healthcare system compared to the one in 2019 are also included, highlighting the nature of these changes. Bearing in mind the relatively limited literature in the field of the considerations undertaken in this article, they can be regarded as important, up-to-date, and filling the research gap in this respect. The aim of the study was achieved using a critical analysis of the literature on the subject and a diagnostic survey. Empirical data were obtained from fieldwork conducted among staff of public and/or private sector healthcare facilities.
Keywords: health system; medical and non-medical staff; survey